World book 2001. Vol. 22 Research guide Index / Mary Alice Anderson - Anderson, Mary Alice (2001)
Guide to writing, writing tips, preparing a short report, book, research, paper, preparing a speech, rehearsing and delivering a speech, guide to research skills, getting to snow, the library, reference and source materials, preparing source cards, taking nortes, using other sources, related information.